Introduction to post-processing techniques - Jiru, Filip (European journal of radiology, 2008)
The quality of data measured in in vivo MR spectroscopy is often insufficient due to a number of limitations such as low concentrations of observed metabolites and restricted measurement time resulting in a low signal-to-noise ratio. However, there are a variety of methods called post-processing techniques which allow the enhancement of the measured signal after measurement. In this review an introduction to the most important post-processing techniques for (1)H MR spectroscopy is given and practical examples are shown. In the first section the concept of FID and spectrum is introduced and the relationship between FID and spectrum is explained. Subsequently, the objectives and description of the following post-processing techniques are provided: eddy current correction, removal of an unwanted component (water), signal filtering for various purposes, zero filling, phase correction and baseline correction.
Keywords: algoritmy; Signal Processing, Computer-Assisted; Artifacts; počítačové zpracování signálu; Body Water; tělesná voda; Humans; Magnetic Resonance Spectroscopy; artefakty; lidé; Algorithms; magnetická rezonanční spektroskopie; Image Processing, Computer-Assisted; Image Enhancement; počítačové zpracování obrazu; vylepšení obrazu